A dynamic performance management approach to frame corruption in public procurement: a case study. Issue 1 (24th March 2021) - Gnoffo, Salvatore
Abstract : Purpose: The purpose of this paper is to frame the causal relationships between corruption in public procurement and performance of local governments. Design/methodology/approach: An outcome-based dynamic performance management approach is adopted to explore a representative case study of a small Italian municipality. The model is based on three sources: qualitative primary data generated by face-to-face convergent interviews; secondary data retrieved from documents describing legal cases linked to procurement and open-access repositories; and an extensive literature review. Findings: Emphasizing the role of community civic morality systemically may help to understand some counterintuitive results in the past research and support decision-makers and policymakers in setting effective strategies to curb the associated negative implications. Social implications: A dynamic approach of performance management aimed at framing corruption in public procurement may guide policymakers and decision-makers in keeping their "cognitive radar" constantly active, in a way to detect emerging corruptive phenomena that could be otherwise ignored by normal diagnostical approaches. It may also help to promote organizational ethical learning and improve community outcomes. Originality/value: This research provides a causal and systemic framework of relationships involving local government performance and wrongdoings in public procurement, by including performance risk indicators linked to structural and individualistic causes of corruption.